Mônada e mundo em Leibniz - Bonneau, Cristiano (2006)
This writing concerns the study of Leibnizs concept of the Monad. Therefore, the present work investigated the fundamental constituents which take part on such a concept. From the notions of attribute, we have perceptions, appetites and apperceptions, as well as the notions of possibility and representation that are present in the Monad, resulting in the idea of World. Such an idea also plays an important role in this writing. The idea of Monad and the idea of World generate relations and structures that were considered as well. Thus, the elements forming the process of knowledge (understanding and language) and the basic components of the Monad (e.g. the idea of substance) were studied according to Leibnizian concept of world. Furthermore, in our analysis of fundamental principles leading to a cosmological, epistemological and ontological perspective in Leibniz, we used a metaphysical approach.